Forest Trees - Kole, Chittaranjan (Genome Mapping and Molecular Breeding in Plants ;, 2007)
Genome Mapping and Molecular Breeding in Plants presents the current status of the elucidation and improvement of plant genomes of economic interest. The focus is on genetic and physical mapping, positioning, cloning, monitoring of desirable genes by molecular breeding and the most recent advances in genomics. The series comprises seven volumes: Cereals and Millets; Oilseeds; Pulses, Sugar and Tuber Crops; Fruits and Nuts; Vegetables; Technical Crops; and Forest Trees. Forest trees cover one third of the global land surface, constitute many ecosystems and play a pivotal role in the world economy. Despite their importance in the economy, ecology and environment, genetic analysis and breeding efforts have lagged behind. Presented here are chapters on Populus trees, pines, Fagaceae trees, eucalypts, spruces, Douglas fir and black walnut, and a first-ever detailed review of Cryptomeria japonica. Innovative strategies to address the inherent problems of genome analysis of tree species are thoroughly discussed.